2010
DOI: 10.1016/j.bbi.2010.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of immune function in cervical cancer patients during chemoradiation using a novel integrative approach

Abstract: Patients receiving chemoradiation for cervical cancer are at risk for distress, chemoradiationrelated side-effects, and immunosuppression. This prospective randomized clinical trial examined effects of a complementary therapy, Healing Touch (HT), versus relaxation training (RT) and usual care (UC) for 1) supporting cellular immunity, 2) improving mood and quality of life (QOL), and 3) reducing treatment-associated toxicities and treatment delay in cervical cancer patients receiving chemoradiation. Sixty women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
101
0
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 59 publications
0
101
0
11
Order By: Relevance
“…Randomized controlled trials performed in medical settings have shown biofield therapies to be effective in such diverse ways as reducing the immune-compromising effects of radiation through use of Healing Touch with cervical cancer patients (Lutgendorf et al, 2010) and reducing persistent cancer-related fatigue while increasing diurnal cortisol variability towards healthy levels through use of energy chelation treatments with breast cancer survivors . A comprehensive review (Jain & Mills, 2010) of clinical trials involving yoga, Tai Chi, QiGong, meditation, prayer, acupuncture, homeopathy, Therapeutic Touch, Healing Touch, and Reiki attributed the positive health effects to the treatments' interaction with patient biofields.…”
Section: International Journal Of Transpersonal Studies 137mentioning
confidence: 99%
“…Randomized controlled trials performed in medical settings have shown biofield therapies to be effective in such diverse ways as reducing the immune-compromising effects of radiation through use of Healing Touch with cervical cancer patients (Lutgendorf et al, 2010) and reducing persistent cancer-related fatigue while increasing diurnal cortisol variability towards healthy levels through use of energy chelation treatments with breast cancer survivors . A comprehensive review (Jain & Mills, 2010) of clinical trials involving yoga, Tai Chi, QiGong, meditation, prayer, acupuncture, homeopathy, Therapeutic Touch, Healing Touch, and Reiki attributed the positive health effects to the treatments' interaction with patient biofields.…”
Section: International Journal Of Transpersonal Studies 137mentioning
confidence: 99%
“…In recent years, several scientific reports along with clinical trials have shown the useful effects of Biofield Energy Treatment, which has shown enhanced immune function in cases of cervical cancer patients with therapeutic touch [12], massage therapy [13], etc. Complementary and Alternative Medicine (CAM) are recognized therapies by The National Center for Complementary and Integrative Health (NCCIH).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several scientific reports and clinical trials have revealed the useful effects of the Biofield Energy Treatment, which has shown enhanced immune function in cases of cervical cancer patients with therapeutic touch [19], massage therapy [20], etc. Complementary and Alternative Medicine (CAM) therapies are now rising as preferred models of treatment, among which Biofield Therapy (or Healing Modalities) is one approach that has been reported to have several benefits to enhance physical, mental and emotional human wellness.…”
Section: Introductionmentioning
confidence: 99%